Ambition Of Emma Woodhouse In Emma Volume 1 Novel By Jane Austen (1816) : A Psychoanalytic Approach - Kusumaning Tyas, Mahayu Pramesti, Drs. H. Abdillah Nugroho, M.Hum, Nur Hidayat, S. Pd (2013)
Problem of the study is how ambition of Emma Woodhouse as the major character Emma Volume 1 novel by Jane Austen. The objective of the study is to analyze the novel based on structural analysis and psychoanalytic analysis. This study is qualitative study, object this study focuses on the major character in Emma Volume 1 novel namely Emma Woodhouse. Type of data of the study is text taken from two data source : primary and secondary. The primary data source us the main data obtain from the Emma volume 1 by Jane austen‟s. Secondary data source is the supporting data are the some materials and references related the study. The technique of data analysis is descriptive analysis. The results of the study show that: Firstly, the structural analysis of the novel consists of character and characterization, setting, plot, point of view, style, theme are related into solid unity. Secondly, the psychoanalytic analysis shows that some problems of the major character cause the conflict of her mental condition, then develop to become contradiction between id, ego, superego and it brings her into ambition.